PENGARUH SUBSTITUSI TEPUNG KACANG MERAH TERHADAP KUALITAS COOKIES - Zahara SY, Nurul Muna; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
This study aimed to analyze the effect of substituting red bean flour 0%, 25%, 50%, 75% and 100% of the quality of shape, color, aroma, taste and texture of cookies. This type of research is true experimental method completely randomized design with three times the number of panelists penggulangan 30 people, data analysis performed by analysis of variance and Duncan followed with further testing if the results significantly. Results of research on the test levels significantly affected (red bean aroma, sweetness and taste of red beans) and no real influential on the test level (forms a neat, uniform shape, color and texture tawny neat) whereas the hedonic test significantly affected (color brownish yellow and brittle texture) and did not significantly affect the hedonic test (form neat, uniform shape and aroma of red beans). Overall the best value found in red bean flour substitution as much as 50% (X2).Keywords: Red Bean Flour, Cookies, Quality, substitution.